Current situations and discussions in Japan in relation to the new occupational equivalent dose limit for the lens of the eye. (20th July 2017) - Yokoyama, Sumi; Hamada, Nobuyuki; Hayashida, Toshiyuki; Tsujimura, Norio; Tatsuzaki, Hideo; Kurosawa, Tadahiro; Nabatame, Kuniaki; Ohguchi, Hiroyuki; Ohno, Kazuko; Yamauchi-Kawaura, Chiyo; Iimoto, Takeshi; Ichiji, Takeshi; et al.
Abstract: Since the International Commission on Radiological Protection recommended reducing the occupational equivalent dose limit for the lens of the eye in 2011, there have been extensive discussions in various countries. This paper reviews the current situation in radiation protection of the ocular lens and the discussions on the potential impact of the new lens dose limit in Japan. Topics include historical changes to the lens dose limit, the current situation with occupational lens exposures (e.g., in medical workers, nuclear workers, and Fukushima nuclear power plant workers) and measurements, and the current status of biological studies and epidemiological studies on radiation cataracts. Our focus is on the situation in Japan, but we believe such information sharing will be useful in many other countries.